Better sleep for teens in Reykjavík : effects of delaying school start on adolescent sleep - Ágústa Dan Árnadóttir 1991- (2023)
The recommended sleep duration for adolescence aged 14 - 17 years old is 8 - 10 hours each night. Studies have shown that Icelandic teens do not meet that recommendation. Multiple studies have shown that delaying school start times may increase sleep duration and well-being for adolescent students. Other studies have discovered that educational programs may also increase sleep duration for teens. The aim of this study was to compare sleep and well-being variables between groups of Icelandic teens receiving these two interventions. Students in 10th grade (aged 14 - 16) from three schools in Reykjavík participated. In the first group, school start was delayed by 40 minutes and a sleep educational program was administered once a week for the school year of 2022-2023. The second group received the same educational program without school start delay and the third was a comparison group. Sleep was measured with sleep diaries, questionnaires, and scan watches, 2 and 6 months after the school start delay and educational program was implemented. Data was compared between groups. Results showed significantly delayed wake up times with no delay in sleep onset times for students with delayed school start. Students with a delayed school start also showed significantly less social jetlag than other groups. Delayed school start time did however not have a significant effect on average sleep duration or well-being. Implications and possible explanations for these results are discussed as well as directions for future research. Keywords: Adolescence, school start delay, sleep education program, sleep duration.